Can the traditionally managed FMIS in Nepal be strengthen by incorporating groundwater-based irrigation systems? - Neupane, Nilhari; Shrestha, Shisher; Verma, Shilp (Farmer Managed Irrigation System Promotion Trust, 2023)
Farmer Managed Irrigated System (FMIS) which is predominantly surface irrigation system in Nepal irrigates 51% of country’s total surface irrigated area. The FMIS system has a century-old history with a network of irrigation infrastructures and robust institutional mechanisms.